Simvastatin to modify neutrophil function in older patients with septic pneumonia (SNOOPI): study protocol for a randomised placebo-controlled trial - Greenwood, Hannah (Trials, 2014)
BACKGROUND: Community-acquired pneumonia (CAP) is considered the leading cause of death from infectious disease in developed countries, while complications of CAP - sepsis being the most common and challenging - increase the risk of mortality. During the progression of sepsis, a state of neutrophil ‘paralysis’ develops resulting in the impairment of neutrophil anti-microbial functions including: chemotaxis, production of reactive oxygen species, and formation of neutrophil extracellular traps (NETs). Mechanisms underlying defective neutrophil function remain elusive although NET formation has been implicated in the immunosuppression and increased rates of sepsis observed in neonates. There is, however, increasing evidence that statins are able to modulate neutrophil function in sepsis as several systematic reviews have concluded that statins have a role in improving infection-related outcomes and mortality while, in vitro, statins have also been shown to boost NET formation in healthy individuals. METHODS/DESIGN: The ‘SNOOPI’ trial is a phase 4, randomised placebo-controlled trial. The aim of this study is to determine whether oral treatment with simvastatin compared to placebo optimises neutrophil anti-microbial functions in elderly patients with septic pneumonia improving patient outcomes in the elderly. The primary outcome will be NET production within 72 to 96 hours of treatment with simvastatin or placebo measured in response to a number of inflammatory mediators, including IL8, f-Met-Leu-Phe and lipopolysaccharide. Secondary outcomes include neutrophil migratory capacity; reactive oxygen species production; neutrophil phagocytic capacity; safety and tolerability of simvastatin administration within this patient group; biological markers of neutrophil activation, the inflammatory response, alveolar epithelial and endothelial injury; systemic endothelial function biomarkers and pulmonary extracellular matrix degradation. This study aims to recruit 60 patients admitted into Queen Elizabeth Hospital Birmingham NHS-Foundation Trust. DISCUSSION: This study will investigate the ability of in vivo simvastatin therapy to modulate neutrophil anti-microbial functions in CAP-associated sepsis. TRIAL REGISTRATION: EudraCT number: 2012-003343-29 (Trial Registered: 26 November 2012). ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1745-6215-15-332) contains supplementary material, which is available to authorized users.